Oreocharis panzhouensis (Gesneriaceae), a new species from karst regions in Guizhou, China - Cai, Lei; Guo, Ying; Zhang, Rong-Mei; Dao, Zhi-Ling; Wen, Fang (Phytotaxa, 2019)
A new species of Gesneriaceae, Oreocharis panzhouensis, is described and illustrated from Panzhou City, Guizhou Province, China. The new species is morphologically similar to O. cavaleriei and O. forrestii in corolla shape and color, number of stigmas and stamens, but it can be easily distinguished by the shape of leaf blade and calyx, leaf blade indumentum, filament and pistil indumentum and length, and peduncle length.